Mechanisms For The Development Of Natural Scientific Thinking Of Students - Fariddun Izatulloyevich Ochilov (Euro Asian Journal Publishing, 2024)
This article analyzes the mechanism for the development of students’ natural science thinking in the process of teaching academic subjects, and also describes the author’s methods
Keywords: education; science; student; natural scientific thinking